Engendrando diálogos entre Freire e Vigotski na contracorrente da educação neoliberal - Ribeiro, Daniela Dominique (Universidade Federal de São Carlos, 2026)
This study aims to establish a dialogue between Freirean pedagogy and the cultural-historical theory of human development to challenge hegemonic paradigms that govern school organization and teaching-learning processes, focusing on public basic education, the research counters neoliberal notions of innovation, lifelong learning, and meritocracy and seeking to dismantle the presumed neutrality of implicit in dehumanizing worldviews. This qualitative bibliographic research is grounded in the framework of historical-dialectical materialism, in which we utilize a literature review of contemporary scientific production alongside the works of Lev Semionovich Vygotsky and Paulo Freire to weave argumentative strands guided by core thematic dialogues. Through critical analysis, it is observed that while existing literature contributes to the intersection of these theories, the specificities of the current crisis marked by the rapid advance of neoliberal incursions that threaten the right to education reaffirm the necessity of reclaiming the thought of authors rooted in historical and emancipatory perspectives. The study highlights the potential for further exploring the dialogue between convergent core themes in Vygotsky’s and Freire’s conceptions to strengthen the articulation of societal projects, the collective nature of education, and the concept of permanent human formation toward freedom. Based on these interpretations, we propose a reflection on the possibilities of contesting the meanings that permeate public basic education, positioning it as a form of resistance and a site for the production of critical and emancipatory scientific knowledge.
Engendering dialogues between Freire and Vygotsky against the current of neoliberal education
Keywords: Paulo Freire; Vigotski; Educação escolar; Educação pública; Práxis educativa; Neoliberalismo; Vygotsky; Basic education; Public education; Educational praxis; Neoliberalism; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; 4. Educação de Qualidade